Gambaran Pelaksanaan Kewaspadaan Universal di Puskesmas Tanawangko - Sapulete, Margareth R.; Rombot, Dina V.; Monintja, Tyrsa; Rayndi, Chenko (UNIVERSITAS SAM RATULANGI, 2013)
Universal precautions is an efforts undertaken in the framework of preventive protection, and minimize cross-infection among health care workers and patients as a result of direct contact with the patient, or the patient's body fluids, and infected with contagious diseases. The purpose of research is to describe the implementation of the universal precautions in the Tanawangko Health Center. This research is a descriptive study. The results showed all respondents always wash their hands before and after performing medical procedures, all respondents always wash their hands with soap and flowing water, 45.45% of respondents did not use a mask when treat patients, all respondents always use gloves when contact with blood or body fluids, 13.64% of respondents did not use gloves when cleaning medical equipment, all respondents always take steps decontamination and sterilization, all respondents always wash medical equipment after use with soap or detergent, 9.09% of respondents did not close the syringe needle with one hand method, 22.73% of respondents did not dispose needle and other sharps in special containers, 77.27% of the respondents did not dispose of medical waste and non-medical in the trash bin. Keywords: Universal Precautions